Whipple's pancreaticoduodenectomy: perioperative outcomes in a tertiary care hospital in Dhaka, Bangladesh - Hossain, A. B. M. Bayezid; Afroz, Sadia; Shovon, M. Tasnimul Khair; Anjuman, Nabila; Chackraborty, Mitul (International Journal of Research in Medical Sciences, 2021)
Background: Pancreaticoduodenectomy is one of the most complex surgery with significant mortality and morbidity. Though the mortality rate has steadily improved, morbidity continues to be high. The aim of this study was to demonstrate the perioperative outcome following this procedure at our hospital. Methods: This retrospective study was conducted in the department of Surgery, Sir Salimullah medical college and Mitford hospital from July 2018 to December 2019. A total of 29 patients who undergone pancreaticoduodenectomy were included in the study. Preoperative, intra-operative and post-operative data were analyzed with emphasis on the morbidity and mortality rates. None of the operated patients received any types of neoadjuvant therapy. Results: Out of 29 patients who underwent PD, 18 (62.1%) were male and 11 (37.9%) were female with a median age of 53.7 years. The most common (34.5%) age group of the patients were 51-60 years. Jaundice was the commonest (89.7%) presenting symptoms followed by anorexia (75.9%) and abdominal pain (48.3%). Overall complications occurred in 37.9% patients, including wound infections (31.0%) and post-operative pancreatic fistula (6.9%). The post-operative mortality rate was 6.9%. Conclusions: PD still causes considerable morbidity and mortality. With careful patient selection, adequate preoperative preparation, surgical technique, excellent critical care management PD can be performed safely. At our center we have a reasonable volume and our data are comparable to literature data.